Tension Band Wiring through Cannulated Cancellous Screw for Transverse Patellar Fracture - Khan, Md Amgad Hossen; Rashid-Un-Nabi, Quazi Md; Islam, Syed Shahidul; Zarin, Ismet; Mazumder, Md Anayet Karim (Journal of Armed Forces Medical College, Bangladesh, 2024)
Background: One of the commonest orthopedic injuries is Patella fracture. We frequently get and treat it. Different modalities of treatment are available for it. Tension band wiring through two 4mm partially threaded cannulated cancellous screw is an option for patellar fracture stabilization. Objective: To assess the outcome of tension band wiring through two 4mm partially threaded cannulated cancellous screw for closed displaced transverse patellar fractures. Methods: A total of 30 patients with displaced transverse patellar fractures were selected. It is a prospective, observational study and was conducted in NITOR, Dhaka during the period from January 2017 to December 2018. We performed ORIF with tension band wiring through cannulated cancellous Screw (4 mm partially threaded cannulated cancellous screw) for all patients. The Iowa knee evaluation score was used for functional assessment. Results: According to Iowa knee evaluation score, 27 patients had excellent results and 3 patients had good results. Two patients had SSTI and 28 Patients had no complication. Knee stiffness, loss of fracture reduction, implant migration, implant failure were nil. Conclusion: Tension band wiring through cannulated cancellous screw can be considered as an effective method to treat displaced transverse patellar fractures. Outcome may be excellent to good with few complications. JAFMC Bangladesh, Vol 19, No 2 (December) 2023: 29-31